Analisis Pengaruh Evaluasi Pendidikan Perspektif Islam Terhadap Peserta Didik Dalam Pembelajaran PAI Di Sekolah - Ayu Wulandari; Hadiana Nasrullah; Rio Azfa Malik; Safira Puspa Nugraha; Muhamad Parhan; Syahidin Syahidin (Universitas Palangka Raya, 2024)
This research analyzes the impact of educational evaluation from an Islamic perspective on students in learning Islamic Religious Education (PAI) using qualitative methods. The focus of the research involves evaluating education based on Islamic principles, evaluating the extent to which the curriculum and evaluation methods reflect Islamic values. The results of the analysis include aspects of Islamic education evaluation in Islamic Education learning and its consequences on learners' motivation, quality and achievement. The research highlights the importance of Islamic values in PAI evaluation, exploring its effect on learners' motivation through positive reinforcement and rewards. In addition, the impact of evaluation on learners' quality, including the dimensions of religiousness, morality, and social behavior, as well as its relationship with learners' learning achievement are also analyzed. The results of this study provide guidance for the development of educational evaluation methods that are more oriented towards Islamic values, enriching the understanding of learner motivation, quality, and learning achievement in PAI learning in schools.